Improving Air Force depot programming by linking resources to capabilities - Snyder, Don, 1962- (Technical report (Rand Corporation), 2012)
One of the more challenging goals in programming is to link Air Force budget program element investments to operationally relevant capability metrics, then to use these metrics to assess any risk incurred by a proposed program objective memorandum (POM). Previous RAND Project AIR FORCE work developed a set of metrics and framework of analysis for capabilities-based programming and assessment of risks of expeditionary combat support. Because of the success of that work, the RAND Corporation was asked to apply and to extend (as needed) this capabilities based approach to the depot maintenance business areas, specifically focusing on depot purchased equipment maintenance (DPEM) as a first step, and to do so with a methodology that is broadly applicable. DPEM comprises numerous depot-level maintenance and inspection activities on capital assets, as well as storage and other supporting activities that span numerous program elements, budget programs, and appropriations. It funds the bulk of the work done at the Air Force depots that does not involve the repair of spares or the work on modification programs. This report presents an analysis of how to better program for DPEM.